Studies on Extraction and Stability of C-Phycoerythrin From a Marine Cyanobacterium - Ghosh, Tonmoy; Mishra, Sandhya (Frontiers in Sustainable Food Systems, 2020)
Being a naturally produced colorant with fluorescent properties, C-phycoerythrin (CPE) has important food industry applications. However, optimization of extraction and its stability under storage is an aspect which needs further attention. In this study, optimization of CPE extraction from Lyngbya sp. CCNM 2053 was undertaken using response surface methodology (RSM). Preliminary screening suggested a phosphate buffered system with freeze thaw for cell disruption as the most suitable method. 22.40 ± 1.31 mg g−1 CPE and 52.76 ± 0.07 mg g−1 total proteins were extracted using phosphate buffer while freeze thaw method yielded 19.87 ± 0.43 mg g−1 CPE and 58.92 ± 3.49 mg g−1 total proteins. RSM was used to optimize phosphate buffer pH (5.5–8), molarity (0.1–1 M) and number of freeze thaw cycles (2–7). Interaction between buffer molarity and number of freeze thaw cycles was most significant for modeling the responses. Extraction of CPE was highest with pH 8 and low molarity buffers. The predicted values from the equations agreed well with the experimental values, proving the robustness of the model. The stability of the extract was also evaluated at different temperatures, light exposure times and pH values. Results indicated that light exposure should be kept to a minimum while the stability was affected by extreme temperatures and pH. CPE was comparatively stable in a pH and temperature range of 3–8 and 4–40°C respectively.